2021
DOI: 10.3390/antiox10091496
|View full text |Cite
|
Sign up to set email alerts
|

Management of Feline Hyperthyroidism and the Need to Prevent Oxidative Stress: What Can We Learn from Human Research?

Abstract: Feline hyperthyroidism is a clinical syndrome related to an excessive production of thyroid hormones, and it is considered as a spontaneous animal model for human thyrotoxicosis. Many shared features between the feline and the human disease have been identified so far, including pathogenesis, clinical signs, and treatment options. Although methimazole is considered the first-choice drug in both species, several side effects have been described. Furthermore, methimazole could interfere with the oxidative status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
1
2
0
1
Order By: Relevance
“…Oxidative damage and the generation of reactive oxygen species (ROS) in the mitochondria are increased in hyperthyroidism. 39,42,43 Our research also showed that hypothyroidism leads to elevated indicators of oxidative stress in the body, but capsiates can improve oxidative stress in the PCG and NCG groups.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Oxidative damage and the generation of reactive oxygen species (ROS) in the mitochondria are increased in hyperthyroidism. 39,42,43 Our research also showed that hypothyroidism leads to elevated indicators of oxidative stress in the body, but capsiates can improve oxidative stress in the PCG and NCG groups.…”
Section: Discussionsupporting
confidence: 54%
“…Additionally, our study shown that although capsiates can reduce oxidative stress in the PCG and NCG groups, hypothyroidism raises oxidative stress markers in the body. Oxidative damage and the generation of reactive oxygen species (ROS) in the mitochondria are increased in hyperthyroidism 39,42,43 . Our research also showed that hypothyroidism leads to elevated indicators of oxidative stress in the body, but capsiates can improve oxidative stress in the PCG and NCG groups.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Авторы показали, что восстановление эутиреоза на фоне приема метимазола у пациентов с гипертиреозом Грейвса на 10-25 % снижает нагрузку системного окислительного стресса. Однако появляются современные данные о том, что фенотип повышенной базальной продукции митохондриальных АФК в эутиреоидную фазу болезни Грейвса может быть связан и с токсическим эффектом длительного лечения метимазолом, усиливающего окислительно-восстановительный дисбаланс [12,13].…”
Section: таблица 3 зимозан-индуцированная хемилюминесценция нейтрофил...unclassified